Analysis of Symptom Characteristics, Influencing Factors, and Their Predictive Value for Posttraumatic Stress Disorder in Nurses: A Cross-Sectional Questionnaire Study. Issue 11 (30th November 2022) - Xue, Mengxin; Yuan, Yuan; Chen, Hong; Dai, Minghui; Sun, Huiping; Qu, Jiling; Zhou, Ting; Zhou, Jingxin; Qu, Junchao; Bu, Yuan; Ji, Siqi; Hu, Yicheng; et al.
Abstract: Nurses often face a variety of nursing-related stresses, making them more prone to symptoms of posttraumatic stress disorder (PTSD). We aimed to explore symptom characteristics, influencing factors, and their predictive value for PTSD in nurses, so as to prevent the occurrence of PTSD in nurses. This was a cross-sectional study conducted in two tertiary hospitals in Yangzhou. A total of 1290 valid questionnaires were received in our study, and 190 nurses (14.7%) were positive for PTSD symptoms. The results show that individuals with higher scores on the Perceived Stress Scale-10 (PSS-10), Patient Health Questionnaire-15 (PHQ-15), Generalized Anxiety Disorder Scale-7 (GAD-7), and maladaptive cognitive emotion regulation strategies questionnaire (maladaptive CERS) were more likely to experience PTSD symptoms, whereas those with lower scores on the Perceived Social Support Scale (PSSS) were more likely to experience PTSD symptoms. Compared with the PSS-10, PHQ-15, and PSSS, GAD-7 and maladaptive CERS had higher predictive value. This study provided the optimal threshold of relevant factors that may have a positive effect on the prevention of PTSD symptoms. This has guiding implications for active prevention and intervention in some institutions.